Purification on a Recombinant Nucleocapsid Protein of Newcastle Disease Virus Using Expanded Bed Adsorption Chromatography - Tan, Yan Peng (2005)
The purification of histidine-tagged nucleocapsid protein (NP) of Newcastle disease virus (NDV) in expanded bed adsorption (EBA) directly from unclarified Escherichia coli feedstock was investigated. Streamline 925 Column (ID = 25 mm) was used as a contactor and Streamline chelating immobilised with ~ i "ion was used as affinity adsorbent. Unclarified E. coli feedstock of 8% biomass wet mass (w/v) was loaded onto the stable expanded bed. The adsorption properties of the Streamline chelating were investigated by batch adsorption. The adsorption of NP protein onto the Streamline chelating was observed to follow the Langmuir isotherm. Optimal binding and elution conditions for the application of EBA were developed. Batch binding experiments results showed that the optimal pH for adsorption and elution buffer is 8.0. Elution buffer which contained 50 mM imidazole was used to remove the unbound proteins and elution buffer with 350 mM imidazole was used to elute NP protein from the adsorbent. Elution in packed bed column showed that the highest NP protein yield was achieved at a flow velocity of 10 crn/h. The bed expansion characteristics of the Streamline chelating with buffer and unclarified feedstock were determined by visually monitoring the bed height as a function of increasing superficial velocity. The dynamic binding capacity of the adsorbent for NP protein was determined in the expanded bed column to be 2.9 mg/mL adsorbent. These results were used to develop a large scale purification of NP protein in Streamline 25 Column. Xi< performance of a conventional purification methodj racked bed adsorption (PBA) and EBA for the purification of the NP protein from E. coli feedstock was assessed and compared. The conventional way for the recovery of NP proteins involved multiple steps such as centrifugation, precipitation, dialysis and sucrose gradient ultracentrifugation. For the PBA, feedstock clarified by centrifuge was used for column loading, while in EBA; unclarified feedstock was used. The final protein yield obtained in conventional and PBA methods was 1.3% and 5.6% respectively. It was demonstrated that the EBA achieved the highest final protein yield of 9.6% with a purification factor of 6.6. In addition, the total processing time was reduced from 56 h to 7.5 h for EBA compared to that of the conventional method. Within the range of the experimental works, result from this study suggested that EBA technique allowed clarification, concentration and initial purification to be combined into a single step operation. The expanded bed purification for NP protein was efficient and scalable, promising its implementation in the large scale production of proteins